2014
DOI: 10.1371/journal.pone.0100424
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Bone Morphogenetic Protein-2 in Debridement and Impacted Bone Graft for the Treatment of Femoral Head Osteonecrosis

Abstract: The purpose of this study was to compare the clinical outcomes of impacted bone graft with or without recombinant human bone morphogenetic protein-2 (rhBMP-2) for osteonecrosis of the femoral head (ONFH). We examined the effect of bone-grafting through a window at the femoral head-neck junction, known as the “light bulb” approach, for the treatment of ONFH with a combination of artificial bone (Novobone) mixed with or without rhBMP-2. A total of 42 patients (72 hips) were followed-up from 5 to 7.67 years (aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 27 publications
4
56
0
1
Order By: Relevance
“…Therapies using cells [4][5][6], proteins, and other bone growth-promoting substances [2,7,8] have been proposed, and various cell therapies using autologous marrow cells are already being attempted. Non-cellular therapeutic strategies using growth factors have been proposed; however, there has been little progress with regard to the verification of animal experiments, primarily because of the absence of an animal model for femoral head-specific necrosis [9,16] and secondarily because of the lack of a technique to locally deliver the growth factor [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapies using cells [4][5][6], proteins, and other bone growth-promoting substances [2,7,8] have been proposed, and various cell therapies using autologous marrow cells are already being attempted. Non-cellular therapeutic strategies using growth factors have been proposed; however, there has been little progress with regard to the verification of animal experiments, primarily because of the absence of an animal model for femoral head-specific necrosis [9,16] and secondarily because of the lack of a technique to locally deliver the growth factor [17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, non-cellular therapeutic strategies that use growth factors have also been proposed [2,3,7,8]. In an animal study using adult rabbits, we reported that a single local administration of gelatin hydrogel impregnated with recombinant human fibroblast growth factor (rhFGF)-2 not only promoted the regeneration of the necrotic bone but also suppressed the progression of ONFH [9].…”
Section: Introductionmentioning
confidence: 99%
“…After a 2-year follow-up, there was a marked increase in mean HHS from 34 points (range, 22 to 50 points) pre-operatively to 87 points (range, 70 to 90 points) post-operatively (p>0.05). Similarly, a randomized trial by Sun et al [26] evaluated the use of rhBMP-2 with impact NVBG (n=43) compared to NVBG alone (n=36) for the treatment of pre-collapse ONFH. After a mean follow-up of 6 years (range, 5 to 8 years), the authors found a marked difference in survival rates between the control and experimental cohorts (72 versus 82 %, respectively).…”
Section: Use Of Bmpsmentioning
confidence: 99%
“…Finally, little evidence has been reported on osteonecrosis, with four published studies, one of which was comparative [17] and described similar results with or without rhBMPs. No complications or adverse events have been reported in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are two commercially available BMPs, recombinant human rh BMP-2 and rhBMP-7. They have been tested in several preclinical studies showing the ability to induce bone regeneration [9][10][11], and evaluated in clinical trials to treat various bone disorders such as non-unions, open fractures, and osteonecrosis [12][13][14][15][16][17]. The successful application of BMPs led, in July 2002, to the approval by the European Medicines Agency (EMA) of rhBMP-2 (InductOs®) for the treatment of single-level lumbar spine fusion and for acute tibial fractures in adults [18].…”
Section: Introductionmentioning
confidence: 99%